Modelo de avaliação da legitimidade do plano municipal integrado de gerenciamento de resíduos da construção civil - Loch, Patricia (2017)
Due to the importance of the civil construction sector to the world economy and constant concerns about the impact that the activity has on the environment, the Government has been taking actions aimed at minimizing this problem through the enactment of specific legislation. In Brazil, the municipalities are responsible for complying with these laws, which, in order to guarantee the legitimacy of their actions, must comply with and enforce them. In this sense, this study aims to develop a model for assessing the legitimacy of the integrated municipal waste management plan for civil construction. For this, the basic indicators of the model were elaborated through the discourse analysis of the bibliographical survey and Multicriteria Methodology to Support the Constructive Decision. Subsequently they were evaluated through a panel of experts, conducted in two rounds, which also supported the definition of the degree of importance of each indicator. The methods of analysis of the model were constructed based on the method of allocation of weights. The proposed model is composed of seven steps that, in addition to evaluating the legitimacy of the municipalities, allow the proposition of priority actions of municipalities that aim to maximize their levels of legitimacy, through the elaboration of priority action plans. For the evaluation of the proposed model, it was applied in the municipality of Cascavel-PR. It is hoped that this model can be used to verify the level of adequacy of the municipalities in relation to the compliance with the legislation on the integrated management of construction waste.